STRATEGI KOMUNIKASI DIGITAL DI INSTAGRAM @omahwayangklaten - Tessalonika Prita Pramesthi; Maya Sekar Wangi (Solidaritas, 2025)
This study aims to analyze the digital communication strategies implemented by Sanggar Seni Omah Wayang Klaten through its Instagram account @omahwayangklaten using the Social Media Engagement Theory (SMET) framework. The research focuses on five main dimensions: interactivity, reach, timelessness, personalization, and content quality. This research employed a descriptive qualitative method, with data collected through direct observation, in-depth interviews with the account administrator, and documentation of the sanggar’s social media activities. The findings reveal that the potential of Instagram as a medium for promoting traditional arts has not been fully maximized. In the interactivity dimension, audience engagement remains low due to limited prompt responses and minimal use of interactive features. The reach is restricted by low posting frequency, lack of hashtag optimization, and absence of cross-community collaborations. Timelessness is not optimal as many posts are uploaded after the momentum of the events has passed. Personalization is underdeveloped as the content tends to be formal and generic. Meanwhile, content quality is technically adequate but lacks variety in formats and storytelling approaches. The implications of this study indicate the need for a more structured social media management strategy, including increasing content frequency and interactivity, optimizing reach strategies, posting content in real-time, enhancing message personalization, and improving the variety and quality of visual content. By doing so, @omahwayangklaten’s digital communication strategy can be more effective in reaching and engaging audiences, especially younger generations. Keywords: digital communication strategy, social media, Instagram, SMET, Omah Wayang Klaten.